Simultaneous monetary policy announcements and international stock markets response: an intraday analysis - Syed Mujahid Hussain (Bank of Finland, 2010)
This paper investigates the return and volatility responses of major European and the US equity indices to monetary policy surprises using extensive intraday data on 5-minute price quotes along with a comprehensive dataset on monetary policy decisions and macroeconomic news. Our results show that monetary policy decisions generally exert an immediate and significant influence on stock index returns and volatilities in both European US markets. Our findings also indicate that European Central Bank s (ECB) press conferences following monetary policy decisions on the same day have define impacts on European index return volatilities, implying that they convey important information to market participants. However, in contrast to some earlier evidence, we do not find any support for the hypothesis that return volatilities in European and US markets are significantly affected by the path surprises. Overall, our analysis suggests that the use of high frequency data is critical for separating the effects of monetary policy actions from those of macroeconomic news announcements on stock index returns and volatilities.
URN:NBN:fi:bof-20140807596
Keywords: 330